Stress analysis of a pipeline as a hydropower plant structural element - Ćulafić, Stefan (Strojniški vestnik, 2020)
This paper describes pipeline stress analysis, primarilybranch junctions, as a structural element in hydro-power plants. Pipelines are exposed to internal pressure,which is present under working conditions. Analysis of stresses in the pipeline of the hydropower plant is based on analytical, numerical, and experimental methods. In this paper, we will define the critical elements of the pipeline. After that, we will determine critical areas in the branch junction, under experimental conditions, where strain gauges should be installed. The obtained resultsshow that a boiler formula can be efficiently applied in the stress analysis. Also, a correlation between the internal pressure and the maximum circumferential stresses in the elastic zone is given. In the final sections of the paper, the limit value of the internal pressure as a load for which stress in the zone of plasticity appears and the safety factor of the branch junction in the exploitation conditions are determined. The contribution of this work is the unification and deepening of the topic related to the problem of the testing ofhydro-power structural elements.
Keywords: analiza napetosti; branch junction; cevovodi; hidroelektrarne; hydropower plants; mejni tlak; membrane; odcep; pipelines; shell intersection; strength analysis; varnostni faktorji